Design and experiment of the components for soil flow direction control of hilling machine based on EDEM - Tong, Zhenwei; Li, Lianhao; Zhang, Xiuli; Chen, Yong; Liu, Xiaochan; Zhou, Peilin; Xia, Yueqing (International Journal of Agricultural and Biological Engineering, 2022)
Cultivation and hilling are important steps in crop field management and provide an important guarantee of crop quality and quantity. With the aim of addressing how the soil flow direction of a traditional cultivation and hilling machine is difficult to control, and because it is difficult to achieve high ridge soil cultivation, among other issues, the components of the soil flow direction control of a hilling machine was designed. The components of the soil flow direction control consisted of a soil-feeding plough device, spiral knives and guide cover devices, etc. The design and analysis of the guiding parts for the two tools of the soil-feeding plough device and the spiral knife were performed to obtain an appropriate guide wall and helix angle. The guiding principle in the flow direction control components was analyzed. The design of the guide wall adopts the torsional columnar plough surface, and the elementary line angle changes from stable to increasing. The analysis of spiral milling showed that when the spiral angle is large, the milling effect is better. According to the discrete element method, the working part of the machine-soil interaction model was established. EDEM software was used to simulate the control components for the soil flow direction of the hilling machine for compound cutting. The design method with a two-factor comprehensive test was used to study the linear velocity along the outer part of the spiral knife and the influence of the forward velocity of machine of the implement on the soil cultivation effect. The results of the discrete element simulation showed that both the linear velocity along the outer part of the spiral knife and the forward velocity of the machine have extremely significant effects on the transportation of particles to the ridge top and the hilling thickness. Following multiple comparisons of the average hilling thickness with different linear velocities along with the outer spiral knife and different forward velocities of the machine, it is concluded that the performance of the machine is better when the linear velocity along the outer spiral knife is 3.01 m/s and the forward velocity of the machine is 0.7 m/s. The research conclusion had great theoretical value and practical significance for the design of the machine, which worked for cultivation and hilling.Keywords: compound cutting, hilling machine, flow direction control, discrete element method, designDOI: 10.25165/j.ijabe.20221503.5857Citation: Tong Z W, Li L H, Zhang X L, Chen Y, Liu X C, Zhou P L, et al. Design and experiment of the components for soil flow direction control of hilling machine based on EDEM. Int J Agric & Biol Eng, 2022; 15(3): 122–131.